A Distributed Bilateral Resource Market Mechanism for Future Telecommunications Networks - Ruffini, Marco (My University, 2019)
In this paper, we propose a distributed market mechanism powered by the blockchain technology addressing network ownership models in multiple telecommunications networks use cases. The proposed model is based on the smart contract technology and enables transparent and trusted bilateral trades, where trust among the network operators does not exist, and there is no impartial third-party entity who is trusted by all of the participants. We use an open source permissioned blockchain framework called Hyperledger Fabric to investigate the performance of the distributed market mechanism in cloud environments. After running experiments on Hyperledger Fabric, we discuss the practical feasibility and possible design choices of our blockchain approach based on latency, throughput and resource consumption analysis.
IEEE Globecom
PUBLISHED
Keywords: Blockchain; Market; Double auction; Smart contract; Telecommunications operators; Virtual network operators